Afircan studies in income and wealth - Samuel, L.H. (London : Bowes & Bowes, 1963)
This volume presents the papers presented at the Conference. The papers provide an opportunity for a critical stock taking of national income work being done in Africa, as well as the use of national income estimates for policy purposes.
International Association for Research in Income and Wealth.
rpm 25/01/2019
Loans
Keywords: African Studies; Income; Wealth; Africa